2011
DOI: 10.1073/pnas.1108924108
|View full text |Cite
|
Sign up to set email alerts
|

Naturally transmitted segmented filamentous bacteria segregate with diabetes protection in nonobese diabetic mice

Abstract: Vertebrates typically harbor a rich gastrointestinal microbiota, which has coevolved with the host over millennia and is essential for several host physiological functions, in particular maturation of the immune system. Recent studies have highlighted the importance of a single bacterial species, segmented filamentous bacteria (SFB), in inducing a robust T-helper cell type 17 (Th17) population in the small-intestinal lamina propria (SI-LP) of the mouse gut. Consequently, SFB can promote IL-17-dependent immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
345
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 373 publications
(368 citation statements)
references
References 56 publications
17
345
1
1
Order By: Relevance
“…3,6 For example, a recent study highlighted the diabetes protective association with presence of segmented filamentous bacteria (SFB) in NOD mice from different facilities. 7 In a recent study, SFB was however only found to protect NOD males in contrast to females when mono-colonized, and the mice therefore regained the diabetes gender bias which is lost in germ-free conditions. 8 Moreover, Lactobacillus and Bifidobacterium were found in higher abundance in feces from bio-breeding diabetes-resistant (BB-DR) rats before clinical onset of T1D compared with bio-breeding diabetes-prone (BB-DP) rats, which contained more Bacteroides, Eubacterium, and Ruminococcus ssp.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 For example, a recent study highlighted the diabetes protective association with presence of segmented filamentous bacteria (SFB) in NOD mice from different facilities. 7 In a recent study, SFB was however only found to protect NOD males in contrast to females when mono-colonized, and the mice therefore regained the diabetes gender bias which is lost in germ-free conditions. 8 Moreover, Lactobacillus and Bifidobacterium were found in higher abundance in feces from bio-breeding diabetes-resistant (BB-DR) rats before clinical onset of T1D compared with bio-breeding diabetes-prone (BB-DP) rats, which contained more Bacteroides, Eubacterium, and Ruminococcus ssp.…”
Section: Introductionmentioning
confidence: 99%
“…In a mouse model of autoimmune arthritis, germ free mice show attenuation of disease accompanied with lower Th17 cell frequency [26], whereas SFB monocolonization in those mice leads to an increase in Th17 cell numbers in the lamina propria and exacerbation of disease [26]. Contrary to clinical manifestations in EAE and arthritis models [26,27], the presence of SFB-induced lamina propria resident Th17 cells in NOD mice protect mice from diabetes [24]. This might occur as a result of the regulation of Th17 cells in the small intestine [39].…”
Section: Regulation Of Th17 Responsementioning
confidence: 99%
“…While SFB is associated with Th17 cells in NOD mice, no immunopathology is observed in these mice [24]. Th17 cells are not always pathogenic [19,39].…”
Section: Type 1 Diabetesmentioning
confidence: 99%
See 2 more Smart Citations